Containment of a carbapenem-resistant Klebsiella pneumoniae in an intensive care unit during the COVID-19 pandemic - Renhua Li; Zuli Zhang; Zhongjie Wang; Keli Qian (Frontiers in Public Health, 2025)
BackgroundA nosocomial outbreak of carbapenem-resistant Klebsiella pneumoniae (CRKP) occurred in the 20-bed Respiratory Intensive Care Unit (RICU) of a tertiary teaching hospital during the COVID-19 pandemic (December 2022–February 2023). The outbreak was ultimately mitigated through multimodal infection control interventions aligned with WHO multidrug-resistant organism (MDRO) management guidelines.MethodsFollowing index case identification on 10 December 2022, a multidisciplinary outbreak response team implemented comprehensive control measures: Immediate geographic cohorting of CRKP-positive patients with dedicated staff; Enhanced contact precautions including daily chlorhexidine bathing; Tri-daily environmental decontamination using sporicidal agents; Mandatory hand hygiene audits with real-time feedback; Active surveillance through weekly rectal swabs for all RICU admissions. Environmental monitoring encompassed 120 high-touch surfaces sampled weekly.ResultsAmong 42 laboratory-confirmed CRKP cases, 85.7% (n = 36) were identified through clinical specimens and 14.3% (n = 6) via active surveillance. Post-outbreak surveillance revealed two imported CRKP cases detected through admission screening during the three-month follow-up period, both contained without secondary transmission. The increasing patient volume, prolonged use of personal protective equipment (PPE), and influx of new healthcare workers heightened the risk of CRKP transmission. Effective administrative guidance on nosocomial infections, behavioral control, active surveillance culture, environmental cleanliness and antimicrobial management are essential to prevent outbreak.ConclusionThis outbreak demonstrates the viability of containing CRKP transmission in resource-constrained pandemic settings through: rigorous adherence to contact precautions; prospective CRE active surveillance cultures. It is also need to implement antimicrobial stewardship programs in order to reduce the occurrence of microbial resistance.